Analysis of the Effects of Catalytic Converter on Automotive Engines Performance Through Real-Time Simulation Models - Gambarotta, Agostino; Papetti, Viola; Dimopoulos Eggenschwiler, Panayotis (Frontiers in Mechanical Engineering, 2019)
Today restrictions on pollutant emissions require the use of catalyst-based after-treatment systems as a standard both in SI and in Diesel engines. The application of monolith cores with a honeycomb structure is an established practice: however, to overcome drawbacks such as weak mass transfer from the bulk flow to the catalytic walls as well as poor flow homogenization, the use of ceramic foams has been recently investigated as an alternative showing better conversion efficiencies (even accepting higher flow through losses). The scope of this paper is to analyse the effects of foam substrates characteristics on engine performance. To this purpose a 0D “crank-angle” real-time mathematical model of an I.C.Engine developed by the Authors has been enhanced improving the heat exchange model of the exhaust manifold to take account of thermal transients and adding an original 0D model of the catalytic converter to describe mass flows and thermal processes. The model has been used to simulate a 1.6l turbocharged Diesel engine during a driving cycle (EUDC). Effects of honeycomb and foam substrates on fuel consumption and on variations of catalyst temperatures and pressures are compared in the paper.